Cosmopolitismo anticosmopolita, Reafirmación identitaria y tranferts culturels: sobre algunas trayectorias y redes entre el nacionalismo argentino y francés - Luis Miguel Donatello (Nuevo mundo - Mundos Nuevos, 2019)
This article proposes top put in dialogue categories form globalization´s sociological theories with historiographies trends on nationalism. Specifically, counterrevolutionary nationalisms. In this ways it builds a descriptive hypothesis based on three terms: anticosmo cosmopolitism, identity reaffirmation and trasnfert culturel.Following this propose, it shows similitude and differences between three experiences, linked to West European World and Latin America, in general, both France and Argentina in particular. These experiences were in common a reciprocal character and not a one way influence. There are trajectories and networks Integral Roman Catholic’s, maurrasiens and theoreticians of national security.According to this, it argues that cases worked let us elements to understand cases with actual analogies. At the same time, it underlies the place of institutions about, by adhesion or opposition, trajectories and networks will build.In this sense, it proposes a contribution to the dossier where article it´s elevated. This objective is to describe different ways of intellectual and political circulations between Europe and Latin America since 19th century from today. For these reasons, this article focuses on counterrevolutionary nationalisms form 20th century.Finally, from the point of view of political sociology, the conclusions try to work in a comparative framework. Specially, for cases superficially considered as marginal’s.